Prioritizing Democracy: A Commentary on Smith's Presidential Address to the Society for Business Ethics. Issue 1 (January 2020) - Singer, Abraham; Ron, Amit
ABSTRACT: In his 2018 presidential address to the Society of Business Ethics, Jeffery Smith claimed that political approaches to business ethics must be attentive to both the distinctive nature of commercial activity and, at the same time, the degree to which such commercial activity is structured by political decisions and choices. In what we take to be a friendly extension of the argument, we claim that Smith does not go far enough with this insight. Smith's political approach to business ethics focuses solely on the outcomes of political choices. But if we think of politics in terms of processes—as in, ongoing disagreement and contest—and not merely a series of legal, administrative, or institutional outcomes, a different view of business ethics emerges. In particular, we argue that such an emphasis points us toward seeing business actors as having a normative duty to preserve the integrity and functioning of democracy.